2010
DOI: 10.1111/j.1399-3062.2010.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of a screening protocol for polyoma virus results in a decreased rate of opportunistic non‐BK viral disease after renal transplantation

Abstract: Monthly PCR monitoring for BK viremia, together with a modest decrease in immunotherapy, is not only safe but also effectively prevents PVN and is associated with a significantly decreased rate of CMV and EBV disease in renal transplant patients. BK viremia may also serve as a surrogate marker for overimmunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…At our center, we follow a screening regimen described by Koleilat et al [20] screening patients monthly during the first year in an effort to improve early diagnosis [20]. In this study, BK viremia prevalence was 18% [20]. This is consistent with the described incidence of BK viremia in renal transplant recipients (10-20%; [8,23]) Importantly, we choose to intervene at plasma BKV loads of log 3 or greater.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…At our center, we follow a screening regimen described by Koleilat et al [20] screening patients monthly during the first year in an effort to improve early diagnosis [20]. In this study, BK viremia prevalence was 18% [20]. This is consistent with the described incidence of BK viremia in renal transplant recipients (10-20%; [8,23]) Importantly, we choose to intervene at plasma BKV loads of log 3 or greater.…”
Section: Discussionsupporting
confidence: 57%
“…Since 2006, we have utilized a monthly screening policy for all transplant recipients with concomitant 50% reduction in MMF dose with a positive result which we define as log 3 copies/ml (1000 copies/ml) in 2 consecutive blood draws by realtime PCR [19]. Additionally, we found that monthly PCR monitoring for BK viremia, with reduction of immunosuppression resulted in not only improved results, but also decreased rates of cytomegalovirus-(CMV) and Epstein Bar Virus-related (EBV) disease, furthering the idea that BK viremia in addition to its pathologic effects can serve a surrogate marker for excessive immunosuppression [20].…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…This finding was further corroborated by Reischig and colleagues who demonstrated reduction in risk of subsequent BK in the setting of antecedent CMV viremia (HR 0.5, P = .018) . Koleilat et al also found a significantly higher incidence of opportunistic EBV or CMV in a historical cohort without BK as compared to those who developed BK viremia ( P = <.05) . While these studies corroborate the findings of our study, they were not designed to specifically assess the impact of BK viremia on subsequent CMV infection.…”
Section: Discussionmentioning
confidence: 99%